2005
DOI: 10.1161/01.hyp.0000153317.06072.2e
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate Prevents the Development of Angiotensin II–Dependent Hypertension in Mice

Abstract: Abstract-Previous studies have indicated that the production of 20-hydroxyecisatatraenoic acid (20-HETE) is similar in the liver of C57/B6 mice and rats, but the renal production of 20-HETE is very low in this strain of mice. The present study examined the effects of induction of the renal production of 20-HETE with fenofibrate (FF) on the development of angiotensin II (Ang II)-dependent hypertension in C57BL/6J mice. The mice were divided into 4 groups and treated with vehicle (control), FF (90 mg/kg per day,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 34 publications
2
56
0
Order By: Relevance
“…20-HETE is currently characterized as a prohypertensive eicosanoid, and has the potential to play a dual role in the regulation of blood pressure by virtue of its ability to induce contraction, as well as to inhibit sodium reabsorption (reviewed in Reference 59). The global consequences of enhanced renal 20-HETE production seem more closely related to prevention than aggravation of hypertension, as increased renal 20-HETE production after fibrate treatment has been linked to CYP -hydroxylase induction and attenuation of angiotensin II-induced, 60 as well as desoxycorticosterone acetate salt-induced hypertension 61 in mice. Also, inhibitors of 20-HETE formation promote salt-sensitive hypertension in rats.…”
Section: Eets and Hypertensionmentioning
confidence: 99%
“…20-HETE is currently characterized as a prohypertensive eicosanoid, and has the potential to play a dual role in the regulation of blood pressure by virtue of its ability to induce contraction, as well as to inhibit sodium reabsorption (reviewed in Reference 59). The global consequences of enhanced renal 20-HETE production seem more closely related to prevention than aggravation of hypertension, as increased renal 20-HETE production after fibrate treatment has been linked to CYP -hydroxylase induction and attenuation of angiotensin II-induced, 60 as well as desoxycorticosterone acetate salt-induced hypertension 61 in mice. Also, inhibitors of 20-HETE formation promote salt-sensitive hypertension in rats.…”
Section: Eets and Hypertensionmentioning
confidence: 99%
“…Our previous studies observed an increased plasma 8-isoprostane level and NAD(P)H oxidase activity in L-NAME-induced high blood pressure, which was blunted by bezafibrate [2] . In a similar study fenofibrate reduced blood pressure in mice with an implanted osmotic mini-pump releasing AII through increased cytochrome P450 metabolite [33,34] . Other groups in our laboratory have also reported lowering effect of clofibrate on L-NAME induced high blood pressure in rats through modulation of NO and AII receptor [30] .…”
Section: Discussionmentioning
confidence: 99%
“…16 PPARa is also well known as a determinant of the development of hypertension and renal damage, especially in AT-II-induced hypertensive rats. 21,23,24,30 Induction of the renal expression of CYP4A enzymes in the kidney using fibrate compounds has been reported to lower BP in SHR, stroke-prone SHR and Dahl salt-sensitive rats. 31,32 We found the inverse pattern of PPARa expression in kidneys of WKY-HF rats compared with that in SHR-HF animals.…”
Section: Discussionmentioning
confidence: 99%
“…It does so through NO production, oxidative stress and cytochrome P450-derived eicosanoids in the kidney. 23,24 Therefore, in this study, we investigated the role of fenofibrate on renal lipotoxicity associated with hypertension and renal inflammation using spontaneously hypertensive (SHR) rats fed a high-fat (HF) diet.…”
Section: Introductionmentioning
confidence: 99%